Evaluation of the score of lacrimal symptom questionnaire (LAC-Q), fluorescein dye disappearance test and endoscopic dye transit test in epiphora - Noor, Arjamilah Mohamed (2023)
Introduction Epiphora attributable to delayed tears drainage is one of the most common complaints encountered in ophthalmology clinics. The aim of this study was to compare the mean score of lacrimal symptom and its social impact using Lacrimal Symptom Questionnaire (Lac-Q), the mean grading of Fluorescein Dye Disappearance Test (FDDT), and the mean time of Endoscopic Dye Transit Test (EDTT) in epiphora patients with partial nasolacrimal duct obstruction (NLDO) and in a control group and to evaluate its correlation. Methods The comparative cross-sectional hospital-based study included 52 adult patients with epiphora and 52 adult patients without epiphora as controls aged 18 years and above. All recruited patients underwent syringing test to evaluate the patency of the lacrimal drainage system. The severity of lacrimal symptom and its social impact was evaluated using a validated Lac-Q questionnaire. FDDT and EDTT were performed in all patients. Results There was a statistically significant difference between mean total Lac-Q score, mean FDDT grading, and mean EDTT time between epiphora patients with partial NLDO and control group (p < 0.01). There was a strong correlation demonstrated between mean total Lac-Q score with mean FDDT grading (r = 0.728, p = < 0.01), and mean EDTT time (r = 0.820, p = < 0.01) in epiphora patients with partial nasolacrimal duct obstruction. Conclusions There was statistically different in the mean score of lacrimal symptom questionnaire, the mean grading of FDDT and the mean time of EDTT in patients with partial NLDO compared to control group. There was strong correlation between FDDT and EDTT with the symptoms of lacrimal outflow obstruction in partial NLDO.